HUKUM ISLAM DAN PERUBAHAN SOSIAL - Faisol, Muhammad (JURIS (Jurnal Ilmiah Syariah), 2019)
It is undeniable that the dynamics of social and Islamic law are intertwined in forming a change. On the one hand, the dynamics and social change occur because of the influence of Islamic law, and in one side the social change affects the development and change of Islamic law. The inscription shows that the Islamic law brought by the prophet Muhammad SAW. has clearly changed the social community order at the time. Social conditions based on poor customs and habits have turned into a society based on Islamic law. Therefore, it can not be denied the change of law because of social change as affirmed in the rule of fiqh. This also demonstrates the nature of Islamic law that always matches the development of the times.